Photonic Band Structure of Fibonacci Superlattices with Metamaterials. Part 2: The Algebraic Method of Calculation for Absorptive Metamaterial Layers - Tarnowski, Karol; Salejda, Wlodzimierz (Photonics Letters of Poland, 2009)
We investigate the properties of the photonic band structure (PBS) of Fibonacci superlattices (FS) containing metamaterial absorptive layers. We study the properties of the PBS by the transfer matrix method (TMM). The energetic transmission coefficient for polarized light falling oblique on finite and binary FS placed in free space is calculated. The numerical results concerning transmission bands and energetic absorption coefficient are presented. The existence of fractal properties of PBS, and so called zero- gaps are confirmed in moustaches- like transmission spectra. The absorption effects are also discussed. Full Text: PDF References: S. A. Ramakrishna, T. M. Grzegorczyk, "Physics and Applications of Negative Refractive Index Materials", SPIE Press and CRC Press 2009 Eds. C. M. Krowne, Y. Zhang, "Physics of Negative Refraction and Negative Index Materials", Springer 2007 W. Steurer, D. Suter-Widmer,"Photonic and phononic quasicrystals", J. Phys. D: Appl. Phys. 40, R229 (2007)[CrossRef] A. Bruno-Alfonso, E. Reyes-Gomez, S.B. Cavalcanti, L.E. Oliveira,"Band edge states of the ?n?=0 gap of Fibonacci photonic lattices", Phys. Rev. A, 78, 035801 (2008)[CrossRef] F. F. de Medeiros, E. L. Albuquerque, M. S. Vasconcelos,"Transmission spectra in photonic band-gap Fibonacci nanostructures", Surface Science, 601, 4492 (2007)[CrossRef] H.X. Da, C. Xu, Z.Y. Li,"Omnidirectional reflection from one-dimensional quasi-periodic photonic crystal containing left-handed material", Phys. Lett. A, 345, 459 (2005)[CrossRef] J. Li, D. Zhao, Z. Liu,"Zeron- photonic band gap in a quasiperiodic stacking of positive and negative refractive index materials", Phys. Lett. A, 332, 461 (2004)[CrossRef] K. Tarnowski, W. Salejda, M. H. Tyc,"Propagation of polarized light through optical nanosuperlattices", Optica Applicata, 37, 387, 2007 M.H. Tyc, W. Salejda, A. Klauzer-Kruszyna, K. Tarnowski,"Photonic band structure of one- dimensional aperiodic superlattices composed of negative refraction metamaterials", SPIE Proceedings Series, 2007, 6581, 658112[CrossRef] M.H. Tyc, W. Salejda, A. Klauzer-Kruszyna, K. Tarnowski,"Propagation of polarized light through superlattices composed of left- and right-handed materials", SPIE Proceedings Series, 2007, 6581, 658113[CrossRef] W. Salejda, A. Klauzer-Kruszyna, M. H. Tyc, K. Tarnowski,"One-dimensional photonic quasicrystals: application to Bragg reflectors", SPIE Proceedings Series, 2005, 5950, 59501Q[CrossRef] W. Salejda, A. Klauzer-Kruszyna, M. H. Tyc, K. Tarnowski,"Electromagnetic wave propagation through aperiodic superlattices composed of left- and right-handed materials", SPIE Proceedings Series, 2005, 5955, 595514[CrossRef] A. Klauzer- Kruszyna, W. Salejda, M.H. Tyc,"Polarized Light Transmission through Generalized Fibonacci Multilayers. I. Dynamical maps approach", Optik, 115, 257 (2004) A. Klauzer- Kruszyna, W. Salejda, M.H. Tyc,"Polarized Light Transmission through Generalized Fibonacci Multilayers. II. Numerical Results", Optik, 115, 267 (2004) P. Yeh, "Optical Waves in Layered Media", Wiley-Interscience 2005